The influence of Green Marketing on Decision Purchasing Organic Products with Interests of Buying as an Intervening Variable at Manado City, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2018)
This research attempts to test and analyze the influence of green marketing on the customers’ decision to buy organic product with the interest to buy as an intervening variable. This is an explanatory research with quantitative method and survey method. The modelling refer to the theories of marketing mix and planned behaviour. The research population are customers who buy organic products at the supermarket or modern market in Manado city, Indonesia. The samples are 120 respondents. The sampling was conducted by purposive sampling technique and data analysis techinique. It also involves confirmatory factor analysis and path analysis, with SPSS 18 application. The result shows following facts: green marketing does not have direct and significant influence on customers’ buying attitude; green marketing does not have direct and significant influence on customers’ purchase decision; buying interest has direct and significant influence on the customers’ decision; green marketing does not have direct and significant influence on customers’ decision with buying interest as the intervening variable.